Spectrophotometric Determination of Ketotifen Drug in Pure form and Pharmaceutical Preparation Using Bromothymol Blue Via Ion-Pair Formation - Mahmood, Ali Khalil (Al-Nahrain Journal of Science, 2013)
The ion-pair formation method has been applied for the spectrophotometric determination of Ketotifen, in bulk sample and in dosage form. The method is accurate, simple and sensitive depending on the extraction of the formed ion-pair with bromothymol blue (BTB) as a chromogenic reagent in chloroform, use phthalate buffer of pH 3.5. The formed complex show absorbance maxima at 417 nm against reagent blank. The calibration graph is linear in the ranges of 0.3-25 µg.mL-1 with detection limit of 0.213µg.mL-1.The results show the absence of interferences from the excipients on the determination of this drug. The proposed method have been applied successfully for the determination of Ketotifen in pharmaceutical preparations.